Comparative study on the morphology and mechanical strength of induction welding joint of polyetheretherketone under different currents. Issue 11 (15th September 2020) - Wang, Feiyun; Ma, Wanping; Zhan, Xiaohong; Zhang, Pingze; Bu, Hengchang
Abstract: There is an increasing need for joining technologies of polyetheretherketone (PEEK), in which induction welding technique is one of the most promising methods. The induction welding experiment of PEEK thin plates was conducted under different input currents in this research, while metal meshes were selected as induction components. The analysis of morphology, microstructure, and elemental composition of welding joints was performed by optical microscope (OM), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS). Moreover, the mechanical strength of the induction‐welding joint was investigated by tensile test. The results indicate that the PEEK can be joined effectively when the metal mesh is selected as an induction component, and the welding joints with good appearance are formed under the appropriate process parameters. The more induced joule heat produced by the higher input current promotes the resin fusion at the interface, which is propitious to reduce the generation of defects. However, the excessive heat input results in the extreme melting and thermal decomposition of PEEK resin, which will deteriorate the morphology and property of the welding joints. When the input current is 5.2A, the induction‐welding joint can reach a maximum mechanical strength of 125.63 MPa, which increases by almost 60.55% through the optimization of welding parameters. Abstract :